Emerging role of gut microbiota in autoimmune diseases - Wang, Xinyi; Yuan, Wei; Yang, Chunjuan; Wang, Zhangxue; Zhang, Jin; Xu, Donghua; Sun, Xicai; Sun, Wenchang (Frontiers in Immunology, 2024)
Accumulating studies have indicated that the gut microbiota plays a pivotal role in the onset of autoimmune diseases by engaging in complex interactions with the host. This review aims to provide a comprehensive overview of the existing literatures concerning the relationship between the gut microbiota and autoimmune diseases, shedding light on the complex interplay between the gut microbiota, the host and the immune system. Furthermore, we aim to summarize the impacts and potential mechanisms that underlie the interactions between the gut microbiota and the host in autoimmune diseases, primarily focusing on systemic lupus erythematosus, rheumatoid arthritis, Sjögren's syndrome, type 1 diabetes mellitus, ulcerative colitis and psoriasis. The present review will emphasize the clinical significance and potential applications of interventions based on the gut microbiota as innovative adjunctive therapies for autoimmune diseases.